GAMIFICATION-ASSISTED FLIPPED LEARNING IN EFL READING CLASSROOM: A CASE OF SECONDARY SCHOOL IN INDONESIA - Riani Noor Yoshania; Fazri Nur Yusuf; Hanna Sundari (Indonesian EFL Journal, 2023)
World Bank's report in Program for International Student Assessment, found that during the first four years of school closures in Indonesia due to the Covid-19 pandemic, school students experienced an 11-point decline in reading skills and learning outcomes. This research focused on gamification-assisted flipped classrooms and how they improved EFL students' reading comprehension. A total of 20 third-year students from a secondary school were chosen purposefully as research participants, since they had the required characteristics. This research designed for qualitative data collection and analysis methodologies in a case study. The learning outcome scores obtained from tests that include questions about micro and macro reading comprehension skills revealed, the average score of pretest was 54, and the post-test was 87, this indicated that gamification assisted-flipped classrooms improved learning reading comprehension skills. According to findings of interviews, questionnaires and observation based on the Technology Acceptance Model regarding students' perceptions of gamification-assisted flipped classrooms, has a relatively high acceptance scale in terms of perceived usefulness, perceived ease of use, behavioral intention, and actual usage. The perceived usefulness has the highest scale, 85.82% of students believe that using Gamification in a flipped classroom improved their performance in reading comprehension. Further research is needed to determine the gamified flipped classrooms can be utilized to improve other english skills.Keywords: EFL students; flipped classroom; gamification; reading comprehension; technology acceptance model.